2002
DOI: 10.1002/mus.10037
|View full text |Cite
|
Sign up to set email alerts
|

Titin and nebulin content in human skeletal muscle following eccentric resistance exercise

Abstract: We measured titin and nebulin content in muscle biopsies from the vastus lateralis before and 24 h after one bout of high-intensity eccentric knee extensor resistance exercise in seven men (26 +/- 3 years). Titin and nebulin content were significantly (P < 0.05) reduced after exercise by 30 and 15%, respectively. These results suggest that the structural components of the myofibrillar apparatus are degraded following high-intensity eccentric resistance exercise in humans. Loss of these proteins may have import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Unlike this investigation, most (20 of 22) of our subject population expressed both titin isoforms. The presence of two titin isoforms is consistent with previous findings in humans (9,25,28,29,37). Fry et al (10) showed that five of 15 subjects expressed both T1 and T2 isoforms.…”
Section: Controlssupporting
confidence: 86%
See 2 more Smart Citations
“…Unlike this investigation, most (20 of 22) of our subject population expressed both titin isoforms. The presence of two titin isoforms is consistent with previous findings in humans (9,25,28,29,37). Fry et al (10) showed that five of 15 subjects expressed both T1 and T2 isoforms.…”
Section: Controlssupporting
confidence: 86%
“…For this reason, strict care was taken in the processing of muscle samples as explained previously by Granzier et al (15). We feel confident that our muscle processing resulted in optimized native titin isoform composition, since the appearance of two bands in human skeletal muscle is similar to that found by others (9,28,29,37). Another property of titin that may have been ignored by the current, and other studies of exercise training in humans, is that titin phosphorylation can also affect stiffness of this protein (18).…”
Section: Controlsmentioning
confidence: 60%
See 1 more Smart Citation
“…Given that titin anchors myosin to the Z-disc, these observations suggest that titin could be damaged after eccentric exercise. Recent studies of human muscle biopsies taken after eccentric exercise have shown changes in the contents of titin and other myofibrillar protein components such as alpha-actin and desmin (26,31). These changes were thought to reflect myofibrillar remodeling rather than myofibril damage.…”
Section: Discussionmentioning
confidence: 98%
“…Titin content was reduced due to direct damage or degradation of titin following a single high-intensity eccentric resistance exercise of human M. vastus lateralis (Trappe et al, 2002). However, Lehti et al (2009) reported no change in titin mRNA expression 2 days after fatiguing jumping exercise.…”
Section: Introductionmentioning
confidence: 95%